2021
DOI: 10.1371/journal.pone.0256971
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid approach to forecast the COVID-19 epidemic trend

Abstract: Studying the progress and trend of the novel coronavirus pneumonia (COVID-19) transmission mode will help effectively curb its spread. Some commonly used infectious disease prediction models are introduced. The hybrid model is proposed, which overcomes the disadvantages of the logistic model’s inability to predict the number of confirmed diagnoses and the drawbacks of too many tuning parameters of the SEIR (Susceptible, Exposed, Infectious, Recovered) model. The realization and superiority of the prediction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The difference in daily average AQI has gradually decreased when compared to the same period in previous years. This study also clarifies how to manage the quality of the air we breathe [38]. The findings show that a temporary social blockade cannot reduce pollution from all sources.…”
Section: Change Of Nomentioning
confidence: 52%
See 1 more Smart Citation
“…The difference in daily average AQI has gradually decreased when compared to the same period in previous years. This study also clarifies how to manage the quality of the air we breathe [38]. The findings show that a temporary social blockade cannot reduce pollution from all sources.…”
Section: Change Of Nomentioning
confidence: 52%
“…The progressive application of the aforementioned strategies has reduced urban pollution sources and pollutant emissions that affect ambient air quality. However, due to restricted management and a rather dense population, the demand for heating expanded tremendously [36][37][38]. As a result, the concentration of particulate matter in Jiangsu increased slightly after traffic restrictions were implemented.…”
Section: Change Of Nomentioning
confidence: 99%
“…The SEIR model can simulate population shifts resulting from infectious disease outbreaks. According to Nawaz et al (38), if the number of confirmed COVID-19 diagnoses each day (I) is projected, the number of healthy persons (S), exposed people (E), and infected people (I) need to be computed. It is also necessary to examine the number of recovered persons (R), the infection rate of healthy people becoming latent, the infection rate of exposed people getting infected, and the recovery rate of diseased people.…”
Section: Logistic and Seir Hybrid Modelmentioning
confidence: 99%
“…However, the continuous loss of agricultural labor in recent years has led to a substantial increase in the cost of manual picking. The problem became more prominent after the COVID-19 pandemic ( Nawaz et al., 2021 ). Therefore, efficient picking machines are a current research focus and an area of importance in orchard intelligence.…”
Section: Introductionmentioning
confidence: 99%